Efficacy of mirror therapy and virtual reality therapy in alleviating phantom limb pain: a meta-analysis and systematic review. Issue 2 (18th January 2022) - Rajendram, Christopher; Ken-Dror, G; Han, T; Sharma, P
Abstract : Introduction: Amputations result from trauma, war, conflict, vascular diseases and cancer. Phantom limb pain (PLP) is a potentially debilitating form of chronic pain affecting around 100 million amputees across the world. Mirror therapy and virtual reality (VR) are two commonly used treatments, and we evaluated their respective success rates. Methods: A meta-analysis and systematic review was undertaken to investigate mirror therapy and VR in their ability to reduce pain levels. A mean difference (MD) model to compare group pain levels pretreatment and post-treatment via aggregating these results from numerous similar studies was employed. Meta-analysis was conducted using RevMan (V.5.4) and expressed in MD for visual analogue scale (VAS) score. Results: A total of 15 studies met our search criteria; they consisted of eight mirror therapy with 214 participants and seven VR including 86 participants, totalling 300 participants. Mean age ranged from 36 to 63 years, 77% male, of which 61% were lower body amputees. Both led to a VAS reduction (mirror therapy mean reduction VAS score was 2.54, 95% CI 1.42 to 3.66; p<0.001; VR 2.24, 95% CI 1.28 to 3.20; p<0.001). There was no statistically significant difference in pain alleviation between mirror therapy and VR (p=0.69). Conclusions: Mirror therapy and VR are both equally efficacious in alleviating PLP, but neither is more effective than the other. However, due to small sample size and limited number of studies, factors such as gender, cause of amputation, site of limb loss or length of time from amputation, which may influence treatment success, could not be explored.